2005
DOI: 10.1007/11561927_22
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Computing with Imperfect Randomness

Abstract: Randomness is a critical resource in many computational scenarios, enabling solutions where deterministic ones are elusive or even provably impossible. However, randomized solutions typically assume access to a source of unbiased, independent coins. Physical sources of randomness, on the other hand, are rarely unbiased and independent although they do seem to exhibit somewhat imperfect randomness. This gap in modeling questions the relevance of current randomized solutions to computational tasks. Indeed, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Also, protocols which rely on cryptographic primitives may require sources of perfect randomness [13], whereas in the full information model, lower entropy sources of randomness have been shown to suffice. [17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, protocols which rely on cryptographic primitives may require sources of perfect randomness [13], whereas in the full information model, lower entropy sources of randomness have been shown to suffice. [17].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, Goldwasser, Sudan, and Vaikuntanathan [11] were the first to consider this problem. They showed that it is possible to run distributed computing applications (e.g., Byzantine agreement) with imperfect randomness.…”
Section: Network Extractor Protocolsmentioning
confidence: 99%
“…Instead, the proper tool for distributed computing is a network extractor protocol, which was introduced (but left unnamed) by Dodis and Oliveira [10] in the cryptographic context and by Goldwasser et al [16] in the context of Byzantine agreement. The idea is that each processor starts with a weak source, and these weak sources are independent.…”
Section: Network Extractorsmentioning
confidence: 99%
“…For protocols using weak sources, the only results are due to Goldwasser et al [16]. They require all weak sources to have min-entropy rate at least 1/2.…”
Section: Byzantine Agreement and Leader Election With Weak Random Soumentioning
confidence: 99%
See 1 more Smart Citation